MNGI-22. A PROGNOSTIC INDEX TO PREDICT THE RISK OF ACTIVE MONITORING FAILURE FOR INCIDENTALLY-FOUND ASYMPTOMATIC MENINGIOMAS. (5th November 2018) - Islim, Abdurrahman; Mohan, Midhun; Moon, Richard; Rathi, Nitika; Kolamunnage-Dona, Ruwanthi; Brodbelt, Andrew; Mills, Samantha; Jenkinson, Michael
Abstract: BACKGROUND: 30% of meningiomas are incidental findings. There is no consensus on the optimal management (active monitoring, surgery, radiosurgery). OBJECTIVE: Develop a prognostic index to identify patients at risk of active monitoring failure. METHODS: Active monitoring failure was defined as: new symptoms, MRI progression (absolute growth rate 2 cm3/year or absolute growth rate 1 cm3/year + relative growth rate 30%/year) or loss of treatment options. A prognostic model was developed using MRI and patient co-morbidity (Charlson-Index) in a retrospective cohort (2007–2015). RESULTS: 385 patients (403 meningiomas) were studied; mean age was 62.6 years (SD=12.0); 301 (78.2%) were female. Over a median of 36.0 months (range: 3–120), 1688 MRI were performed (mean=4 scans/patient). 44 (10.9%) meningiomas failed active monitoring. Median time to failure was 33.0 months (range: 5–102). Model parameters were based on statistical and clinical considerations and included: increasing tumour volume (HR=2.17 [95% CI=1.53–3.09], p<0.001), peritumoural signal change (HR=1.58 [95% CI=0.65–3.85], p=0.313), FLAIR/T2 hyperintense meningiomas (HR=10.6 [95% CI=5.39–21.0], p<0.001) and proximity to neurovascular structures (HR=1.38 [95% CI=0.74–2.56], p=0.314). Discriminatory power of the model was excellent (Harrells C statistic=0.89). Patients were stratified into low, medium and high-risk groups and rates of failed active monitoring at 5-years were 3%, 28% and 75% respectively. Low-risk patients had non-oedematous, small iso/hypointense meningiomas, distant from neurovascular structures. After 5-years of follow-up, the probability of failed active monitoring plateaued in all risk groups. Older patients with co-morbidities (Charlson-Index 6) were 15-times more likely to die than to receive intervention at 5-years following diagnosis, regardless of risk-group. CONCLUSION: Most meningiomas remain clinically and radiologically stable. Patients with Charlson-Index 6 do not require active monitoring. Low-risk patients require less frequent MRI monitoring. Follow-up beyond 5-years may not be required for all patients. Stratifying follow-up according to risk-group has the potential to reduce the cost of healthcare.